The Determinants of Stock Market Index: VAR Approach to Turkish Stock Market - Eşref Savaş Başçı; Süleyman Serdar Karaca (International Journal of Economics and Financial Issues, 2013)
In this paper, we examined the relationship between ISE 100 Index and a set of four macroeconomic variables using Vector Autoregressive (VAR) model. Variables we used in our model are Exchange, Gold, Import, Export and ISE 100 Index. ISE 100 Index is a dependent variable and the others are independent variables. In this study we used 190 observations for the sample period from January, 1996 to October, 2011. All variables have seasonal movements. After seasonal adjustments, all series have had stationary in their first difference. After determining optimal lag order, it was given one standard deviation shock for each series and their response. And in variance decomposition carried out subsequently, it has been determined that especially as of the second default of exchange, it was explained 31% by share indices.